The embryonic development of the cnidarian Hydractinia echinata. Issue 6 (23rd October 2014) - Kraus, Yulia; Flici, Hakima; Hensel, Katrin; Plickert, Günter; Leitz, Thomas; Frank, Uri
SUMMARY With the rapid increase of the quantity of molecular data, many animals joined the ranks of the so‐called 'emerging models' of Evo‐Devo. One of the necessary steps in converting an emerging model into an established one is gaining comprehensive knowledge of its normal embryonic development. The marine colonial hydrozoan Hydractinia echinata – an excellent model for research on stem cells, metamorphosis, and allorecognition – has been studied for decades. Yet knowledge of its embryonic development remains fragmentary and incomplete. Here we provide a detailed account of H. echinata embryonic development using in vivo observations, histology, immunohistochemistry, and electron microscopy. Furthermore, we propose a model describing the cellular basis of the morphogenetic movements occurring during development and also reveal a functional link between canonical Wnt signaling and regional differences in the morphology of the embryo. Hydractinia embryogenesis is an example of the diversity and plasticity of hydrozoan development where multiple routes lead to the same result – the formation of a normal planula larva.